Phase composition, microstructure, and properties of Al4O4C–(Al2OC)1-x(AlN)x –Zr2Al3C4–Al2O3 refractories prepared at high temperatures in nitrogen. Issue 21 (1st November 2021) - Yan, Mingwei; Zhang, Jiayu; Sun, Guangchao; Liu, Kaiqi; Li, Yong
Abstract: The novel Al4 O4 C–(Al2 OC)1- x (AlN) x –Zr2 Al3 C4 –Al2 O3 refractories with ultra-low carbon content have been successfully prepared by constructing the core-shell structure of aluminum at 1300–1700°C in nitrogen. The phase composition, microstructure, and properties of the novel refractories are deeply investigated. The cracking temperature on the core-shell structure of aluminum is further explored and the reaction mechanism of Zr2 Al3 C4 has also added explanation. The results show that the novel refractories have excellent physical properties and cannot be corroded by molten iron. There exist two different Al2 OC solid solutions in the novel refractories, Al2 OC-rich (Al2 OC)1- x (AlN) x and AlN-rich (Al2 OC)1- x (AlN) x . The temperatures affect their relative content. When temperatures are less than 1600°C, the relative content of Al2 OC-rich (Al2 OC)1- x (AlN) x is more than that of AlN-rich (Al2 OC)1- x (AlN) x . When temperatures are above 1700°C, the relative content of AlN-rich (Al2 OC)1- x (AlN) x is more than that of Al2 OC-rich (Al2 OC)1- x (AlN) x . The core-shell structure of aluminum fully ruptures at about 1200°C. Zr2 Al3 C4 begins to form at about 1000°C and generates in large at 1200°C.